2008
DOI: 10.1590/s0034-72992008000100021
|View full text |Cite
|
Sign up to set email alerts
|

Eletrococleografia extratimpânica na neuropatia/dessincronia auditiva

Abstract: The brainstem auditory evoked potential (BAEP) is being extensively used as a method for the evaluation of cochlear function in individuals with diagnosis of auditory neuropathy/auditory dyssynchrony (AN/AD). In the absence of otoacoustic emissions, many cases of AN/AD have been diagnosed by the presence of CM identified in the BAEP. Aim: to demonstrate the clinical applicability of extratympanic electrocochleography (ET-Ecochg) in the differential diagnosis of AN/AD compared to the BAEP. Method: a 4-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…However, there is little information in the literature on the clinical application of this procedure in cases of ANSD. 35 In the present review, two of the studies analyzed 20 , 25 evaluated the auditory nerve in children with ANSD through MRI and high-resolution CT. One study 20 demonstrated that children with ANSD may show an auditory nerve deficit associated with abnormalities in the inner ear, with worse outcomes in speech perception after CI use. In another study, 19 the authors reported that children with ANSD with a normal cochlear nerve preoperatively demonstrated excellent results in tests of speech perception after CI use.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is little information in the literature on the clinical application of this procedure in cases of ANSD. 35 In the present review, two of the studies analyzed 20 , 25 evaluated the auditory nerve in children with ANSD through MRI and high-resolution CT. One study 20 demonstrated that children with ANSD may show an auditory nerve deficit associated with abnormalities in the inner ear, with worse outcomes in speech perception after CI use. In another study, 19 the authors reported that children with ANSD with a normal cochlear nerve preoperatively demonstrated excellent results in tests of speech perception after CI use.…”
Section: Resultsmentioning
confidence: 99%
“…It is highly recommended to use ECochG to confirm the AS/AN diagnosis [2], but only a few studies to date have investigated the ECochG waveform patterns of this pathology [11,15,[20][21][22][23][24]. Santarelli, for example, used also a transtympanic ECochG with clickstimulation and looked at the adaptation behaviour to rapid stimulus rates in order to determine whether the potentials were of receptor or neural origin.…”
Section: Discussionmentioning
confidence: 99%
“…O local específico da lesão não é definido, mas pode acometer as células ciliadas internas, as sinapses entre as células ciliadas internas e o nervo auditivo (VIII par), o próprio nervo auditivo ou várias dessas estruturas ao mesmo tempo 18 . Os achados na avaliação audiológica nestes casos são EOE-t presentes (função coclear normal) e PEATE ausente ou severamente comprometido 19 . Em estudo realizado com uma população de crianças com perda auditiva profunda, a prevalência de neuropatia auditiva foi de 0,94% 20 .…”
Section: Discussionunclassified